Pemberdayaan Pelaku Usaha Mikro Melalui Bantuan Rombong Baznas Dalam Meningkatkan Pendapatan Di Kota Blitar - Resa Dwi Rahmawati; Anisa Zahwa Fadhila; Elsa Dwi Rahayu; Maulidana Nur Azizah (LP3M IAIFA Kediri, 2026)
Poverty remains a major issue despite a decline in poverty rates in Blitar City. One of the mitigation efforts is carried out through the empowerment of micro, small, and medium enterprises (UMKM), which play a crucial role in increasing community income. However, UMKM still face challenges such as limited capital, business facilities, and human resource quality. BAZNAS Blitar City has introduced the Rombong Assistance Program as a form of productive zakat-based empowerment to support the economic independence of micro-business owners. This study aims to analyze the implementation of the “Rombong” assistance program and its role in increasing the income of micro-business owners in Blitar City. The method used is qualitative with a descriptive approach. Data were collected through interviews, observations, and documentation of beneficiaries and program managers using purposive sampling. The results of the study indicate that the mobile stall assistance program has improved the quality of business facilities, making them more suitable, hygienic, and attractive. However, the resulting increase in business activity has been uneven, influenced by internal factors such as health and skills, as well as external factors such as business location and market conditions. Additionally, some beneficiaries have not yet utilized the assistance optimally. Thus, while the mobile stall assistance program serves as a supportive factor in increasing income, its effectiveness depends on the entrepreneurs’ capabilities and the availability of mentoring support.